2020
DOI: 10.1002/agg2.20056
|View full text |Cite
|
Sign up to set email alerts
|

Mining of soil legacy phosphorus without jeopardizing crop yield

Abstract: Off‐site transport of excess soil P from repeated P fertilizer applications constitutes waste of a vital resource and poses an environmental risk. Excess P can be mined by growing crops without P addition until it is exhausted to the point of P deficiency. This study evaluated the utility of the “soil phosphorus storage capacity” (SPSC) as an indicator of safe P mining for acid soils. The SPSC predicts crop‐available legacy P in absolute terms, (i.e., kg ha−1; can be calculated from mg kg−1 if the bulk density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In these regions, excessive nutrients are typically applied each year leading to excess nutrient build up in the soil, for example, excessive P build up(Griffin et al, 2003;Jokela et al, 2011;Pagliari & Laboski, 2013;Sadeghpour et al, 2017;Toth et al, 2006). Thus, removing excessive nutrients, especially N and P, from the soil is desirable to minimize the likelihood of environmental pollution(Fiorellino et al, 2017;Nair et al, 2020). Therefore, in these regions, the value of nutrients removed by WCR should not be considered as a cost.…”
mentioning
confidence: 99%
“…In these regions, excessive nutrients are typically applied each year leading to excess nutrient build up in the soil, for example, excessive P build up(Griffin et al, 2003;Jokela et al, 2011;Pagliari & Laboski, 2013;Sadeghpour et al, 2017;Toth et al, 2006). Thus, removing excessive nutrients, especially N and P, from the soil is desirable to minimize the likelihood of environmental pollution(Fiorellino et al, 2017;Nair et al, 2020). Therefore, in these regions, the value of nutrients removed by WCR should not be considered as a cost.…”
mentioning
confidence: 99%
“…This suggests that the BMPs tailored to reduce legacy P and improve manure management/applications would be beneficial for those sub-watersheds as well. Nair et al [102] recommended the adoption of a "soil phosphorus storage capacity" to determine the site-specific phosphorus fertilization rates to first exhaust legacy P via crop uptake without impacting productivity. This study in Florida showed promising results as a viable way of mining legacy P through reduced fertilizer applications but could benefit from further research and development.…”
Section: Implications For the Lake Okeechobee Watershedmentioning
confidence: 99%
“…As the function α varies, the initial work of Breeuwsma and Schoumans (1987) to determine PSS has been modified for wider use. First, the acid ammonium oxalate extractant was replaced by Mehlich‐3 extractant, due to the instability of the oxalate solution under normal laboratory conditions (i.e., the oxalate solution has to be kept in the dark), which required the extractant to be made fresh on a daily basis (Kleinman & Sharpley, 2002; Nair et al., 2020; Schoumans, 2009). Soil PSS (percentage basis) was calculated from Mehlich‐3 P (M3P), Al (M3Al), and Fe (M3Fe; mmol kg −1 ) according to Equation : truerightPSS=leftMehlich30.28emnormalextractable0.28emsoilP/31)(Mehlich30.28emnormalextractable0.28emnormalsoil0.28emFe/56+)(Mehlich30.33em0.28emextractable0.28emsoilAl/27left×0.33em100…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have measured PSS for a range of soils in the United States and Europe (Leinweber, Lunsmann, & Eckhardt, 1997; Lookman, Jansen, Merckx, & Vlassak, 1996; Nair et al., 2020; Schoumans & Chardon, 2015), less is known about the effect of land management on PSS under field conditions. This paper describes the effect of P application via mineral fertilizer, swine slurry, and grazing cattle on the PSS of three pastures, which were grid‐soil sampled in 2014, 2016, and 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation